A case of abnormal overvoltages in a Petersen grounded 132-kV system caused by broken conductor. - Gustavsen, B. (IEEE Transactions on power delivery)
This paper analyzes a case where a broken phase conductor in a Petersen grounded system caused extensive damage and outages due to excessive stationary overvoltages. It is shown that the high overvoltages resulted from a combination of the following: (1) the fault occurred on a radial connection, (2) the total compensation was close to 100%, and (3) the compensation of the two subnetworks defined by the fault was far from 100% (one subnetwork was undercompensated and the other overcompensated). Overvoltages calculated by a simple model compare favorably with recorded results. The overvoltages are shown to be strongly dependent on the compensation level, the compensation distribution, the shunt conductance to ground, and the load. A least squares method is used for estimating the shunt conductance based on a measured resonance curve.